Pengaruh Country Of Origin Image, Product Quality, Brand Familiarity Terhadap Consumer Purchase Intention Pada Produk Televisi Sharp - Wulan Aka Yuana; Muhartini Salim; Sularsih Anggarawati (Universitas Bengkulu, 2021)
The purpose of this study is to determine the influence of country of origin, product quality, brand familiarity of consumer purchase intention Sharp television. The type of research used is quantitative research. This study is with primary data. Samples in this study as many 150 respondents who are taken from interested and attention communities will make a purchase intention of Sharp television. The sampling technique using snowball sampling methods of collecting data with online questionnaires. Data analysis using multiple linear regression analysis. The result of this study indicate that the variable of origin country significant 0.000 then effects consumer purchase intention. Product quality value significant level 0,006 then effects consumer purchase intention and brand familiarity value of 0,000 significant level effect consumer purchase intention. This means that the higher purchase intention, the higher country of origin image, product quality and brand familiarity. Therefore, country of origin image, product quality, and brand familiarity have relationship to strengthen the level of purchase intention. the implications of this study will help companies improve purchase intention in sharp television by optimizing country of origin image, product quality, and brand familiarity.